Temperature Dependence of Sensors Based on Silver-Decorated Nitrogen-Doped Multiwalled Carbon Nanotubes. (13th January 2016) - Gracia-Espino, Eduardo; Rebollo-Plata, Bernabé; Martínez-Gutiérrez, Hugo; Muñoz-Sandoval, Emilio; López-Urías, Florentino; Endo, Morinobu; Terrones, Humberto; Terrones, Mauricio
Abstract : Vapor sensors are easily fabricated onto alumina substrates using foils of silver-decorated nitrogen-doped multiwalled carbon nanotubes (CN X -MWNTs-Ag) as active sensing material. The vapor sensors are tested using carbon disulfide, acetone, ethanol, and chloroform vapors. The CN X -MWNTs are produced by chemical vapor deposition process and then decorated with 14 nm Ag nanoparticles (Ag-NPs). The samples are characterized using scanning electron microscopy, transmission electron microscopy, and X-ray diffraction. Our results demonstrate that Ag-decorated CN X -MWNTs exhibit a better response and sensitivity when compared with pristine CN X -MWNTs based sensors, making them promising candidates for air-pollutants environmental monitoring. The temperature effect on the sensor performance is also studied; we found that the detection mechanism could be tuned from physisorption, at room temperature, to chemisorption at higher working temperature. Finally, first-principles density functional calculations are carried out to understand the interactions between the systems involved in the sensors, finding good agreement between experimental results and the theoretical approach.